A2_6 Falling From Hell (In a Cell) - Bradley-Evans, Ryan; Gafur, Razzia; Heath, Ryan; Hough, Matthew (Physics Special Topics, 2017)
We take a look at some of the physics involved in the WWE Wrestlemania 32 Hell in a Cell match between The Undertaker and Shane McMahon. By resolving forces and momentum involved in Shane McMahons fall from the top of the cell and through a table, we calculate the effective impact he feels and compare this to an instantaneous impact (a situation where the table does not break). The reduction in momentum is found to be 943.9 Ns. It is concluded that the table he goes through drastically reduces the impact he would have felt, had it been instantaneous.